Direct HPLC separation of carnosine enantiomers with two chiral stationary phases based on penicillamine and teicoplanin derivatives. Issue 6 (2nd January 2018) - Fumagalli, Laura; Pucciarini, Lucia; Regazzoni, Luca; Gilardoni, Ettore; Carini, Marina; Vistoli, Giulio; Aldini, Giancarlo; Sardella, Roccardo
Abstract: Carnosine is present in high concentrations in specific human tissues such as the skeletal muscle, and among its biological functions, the remarkable scavenging activity toward reactive carbonyl species is noteworthy. Although the two enantiomers show almost identical scavenging reactivity toward reactive carbonyl species, onlyd ‐carnosine is poorly adsorbed at the gastrointestinal level and is stable in human plasma. Direct methods for the enantioselective analysis of carnosine are still missing even though they could find more effective applications in the analysis of complex matrices. In the present study, the use of two different chiral stationary phases is presented. A chiral ligand‐exchange chromatography stationary phase based on N, S ‐dioctyl‐d‐ penicillamine resulted in the direct enantioseparation of carnosine. Indeed, running the analysis at 25°C and 1.0 mL/min with a 1.5 mM copper(II) sulfate concentration allowed us to obtain separation and resolution factors of 3.37 and 12.34, respectively. However, the use of a copper(II)‐containing eluent renders it hardly compatible with mass spectrometry detectors. With the teicoplanin‐based stationary phase, a mass spectrometry compatible method was successfully developed. Indeed, a water/methanol 60:40 v/v pH 3.1 eluent flowed at 1.0 mL/min and with a 25°C column temperature produced separation and resolution factors of 2.60 and 4.16, respectively.